Hajj Title as Motivation and Self-Control for Pilgrims - Famelia, Zella; Mintarsih, Widayat; Murtadho, Ali; Sulistio, Sulistio; Sukma, Hayu Nabila Ma’al (Munazzama: Journal of Islamic Management and Pilgrimage, 2024)
The title of Hajj has many meanings, from cultural, historical, and normative to sociological. However, there is still abuse of the title of Hajj as an economic field and social stratification. This study aims to examine the functionality of the title of Hajj for pilgrims, both as motivation and self-control. This research is a qualitative descriptive method with a phenomenological approach and a psychological scientific approach. The results show that the title of Hajj can function as motivation and self-control for pilgrims, both from internal and external directions, to improve self-quality and control themselves from deviant actions. This research concludes that a Hajj degree can provide functional benefits for pilgrims, such as motivation and self-control in behavior. Hajj is a stronghold for acting and socializing where a person must always consider every word and deed before doing or speaking